Optical Interference Coatings 2010
DOI: 10.1364/oic.2010.tuc5
|View full text |Cite
|
Sign up to set email alerts
|

Optical Admittance Monitor through a Dynamic Interferometer

Abstract: A way to increase the optical monitoring sensitivity in quarterwave stack fabrication by modified optical admittance loci was demonstrated. The optical admittance value was obtained from an in-situ dynamic interferometer combing with a photodetector, and the result was compared with ellipsometer measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that such interferometric measurements can be practically managed within operational deposition chambers [8][9][10]. In particular, the set-up proposed by Lee and coworkers [8,9] seemed to fulfill most of our objectives.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that such interferometric measurements can be practically managed within operational deposition chambers [8][9][10]. In particular, the set-up proposed by Lee and coworkers [8,9] seemed to fulfill most of our objectives.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have shown that such interferometric measurements can be practically managed within operational deposition chambers [8][9][10]. In particular, the set-up proposed by Lee and coworkers [8,9] seemed to fulfill most of our objectives. It uses a polarimetric Michelson interferometer equipped with a micro-polarizer pixelated camera to achieve an instantaneous acquisition of four different phase states of the field reflected or transmitted by the sample [11,12].…”
Section: Introductionmentioning
confidence: 90%